PANDANGAN TOKOH AGAMA KOTA LANGSA TERHADAP PEMAKSAAN HUBUNGAN SEKSUAL - Nairazi, Faisal (LEGALITE, 2017)
Law No. 23 of 2004 on Elimination of Domestic Violence (PKDRT) is one form of government effort to eliminate violence in the family that most of the victims are women. Religious figures state that coercion of sexual intercourse with wife is not allowed in Islam although it is basically obligatory for the wife to serve the husband's request, but if it is not aroused to serve him, he may offer or suspend it. The factors causing the coercion of husband's sexual intercourse with wife are still the dominant patriarchal value in our society (values that prioritize the interests of men). Values that side with men which then form unwritten rules "wife is the property of the husband". A false understanding of the interpretation of the teachings of religions. Frequently the teachings of religions are misinterpreted which affects the differentiation of women's position with men or present discriminatory treatment of women. Then there is the internet media that provides pornographic content that is easily accessible. Perspectives of religious leaders in Langsa City against coercion of sexual intercourse husband to wife is in doing husband relationship of wife need to understanding and know what duty and responsibility respectively, a good husband will not force relationship husband and wife if wife in sick condition, tired or in the coming months. And a wife is not allowed to refuse a husband's invitation if the things mentioned above do not happen to her.